Studies On Immuno-Modulatory Activity of Selected Medicinal Herbs (In-Silico Approach) - Preenon Bagchi; Ajit Kar (International Journal of Pharma and Bio Sciences, 2024)
In recent years, there has been a tremendous development of biotechnological, pharmacological, and medical techniques that can be implemented in the functional modulation of the immune system components. Immuno-modulation is a technique wherein we consider the combined effect of several Ayurvedic herbs. Significant early research studies demonstrate immune modulation. The current trend reported an increase in immuno-modulation studies by ayurvedic herbs. Immunomodulation has attracted much attention because it directly applies to basic research and clinical therapy. Immuno-modulation is gaining significance as a new mode of treatment in pharmacy. The combined effects of several herbs are taken as treatment in immune modulation. In this work, we try to understand the immune modulatory properties of certain ayurvedic herbs. We have taken the FASTQC genome sequence of selected ayurvedic herbs for this study. After quality checking of the sequences, we joined both reads (forward and reverse) using the FASTQ interlaced. It is significant since we need to study the complete sequence (both the reads). Using Velvet software, we identified the K-mers. We took the k-mer coverage to understand the association of the herbs using clustering studies. To understand the immune modulation, we performed principal component analysis and visualized the analysis using a Scree plot and scatter plot. The clustering results of the k-mers are significant in understanding immune modulation. The association results proved the immune modulation property of the ayurvedic herbs.